Drought may be beneficial to the competitive advantage of Amaranthus spinosus. (9th January 2022) - Yu, Youli; Cheng, Huiyuan; Wang, Shu; Wei, Mei; Wang, Congyan; Du, Daolin
Abstract: Drought can affect the growth and soil enzyme activities of invasive alien plants (IAPs). It is imperative to evaluate the competitive advantage of IAPs compared with that of the native species and the activities of soil enzymes under drought. This study aimed to evaluate the competitive advantage of the IAP Amaranthus spinosus that originated from tropical America compared with the native Chinese species A. tricolor and the activities of soil enzymes under drought. A competitive co-culture of A. spinosus and A. tricolor was established using a planting basin experiment. The two species were treated with different levels of drought, i.e. (i) the control; (ii) a light level of drought and (iii) a heavy level of drought. The functional traits, osmotic adjustment and the activities of antioxidant enzymes of the two species, as well as soil pH and electrical conductivity, contents of soil microbial biomass carbon and the activities of soil enzymes were determined. The relative competition intensity and relative dominance of A. spinosus were greater than those of A. tricolor under drought. Drought may provide an advantage to the competitive advantage of A. spinosus . Soil water-soluble salt content and sucrose hydrolytic power of A. spinosus were greater than those of A. tricolor under drought. The ability of A. spinosus to grow in soil with higher levels of water-soluble salt contents and sucrose hydrolytic power under drought may aid in its acquisition and utilization of nutrients.